Effects of elevated atmospheric CO2 and temperature on the management of powdery mildew of zucchini. Issue 7 (28th May 2020) - Gullino, Maria Lodovica; Tabone, Giulia; Gilardi, Giovanna; Garibaldi, Angelo
Abstract: The impact of combined environmental factors, such as temperature and CO2, on the control of the powdery mildew of zucchini, caused by Podosphaera xanthii, and of different control measures has been studied on plants grown in phytotrons. Five experimental trials were conducted, and the powdery mildew severity of both treated and untreated zucchini plants was found to be significantly affected by the interaction between temperature (three different regimes: 16–18; 18–22; 22–26°C), CO2 (two concentrations: 400–450 and 800–850 ppm) and the treatments. However, at the end of the trials, the efficacy of all the products was not affected by the different, tested environmental conditions. Sulphur consistently provided the highest disease control (75%–85% efficacy). Among the resistant inducers that were tested, calcium oxide was the most effective, in terms of powdery mildew control under all the conditions tested in phytotrons, reducing disease severity from 46% to 61%. Foliar applications of phosphite (14%–28% efficacy), Ampelomyces quisqualis (12%–23% efficacy) and potassium silicate (13%–24% efficacy) only slightly reduced the disease severity for all the tested temperature regimes and CO2 concentrations, compared to the untreated control. The results obtained under our experimental conditions show that a possible increase in CO2 concentration and temperature, which is expected for the next few years, should not influence the efficacy of the tested resistance inducers or of sulphur against powdery mildew on zucchini. Moreover, the suppressive effect of calcium oxide is in light of its possible use in greenhouses for zucchini powdery mildew control under 400–450 ppm of CO2 and under enriched condition of 800–850 ppm of CO2 .